2017
DOI: 10.1245/s10434-017-6060-7
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Serum Inflammatory Markers for Predicting Microvascular Invasion and Survival for Patients with Hepatocellular Carcinoma

Abstract: This largest Western series to evaluate the utility of preoperative inflammatory markers in patients with HCC found that only PLR was associated with RFS and OS and that albumin was associated with MVI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 41 publications
2
47
2
1
Order By: Relevance
“…NLR, PLR and LMR are considered systemic inflammatory biomarkers and have been investigated in patients with various types of cancer. High PLR was associated with worse OS and RFS in (mostly non‐cirrhotic) patients with HCC. These findings were not validated by another study, in which both NLR and LMR, but not PLR, were independently predictive of RFS in HCC associated with HBV‐related cirrhosis.…”
Section: Discussionmentioning
confidence: 96%
“…NLR, PLR and LMR are considered systemic inflammatory biomarkers and have been investigated in patients with various types of cancer. High PLR was associated with worse OS and RFS in (mostly non‐cirrhotic) patients with HCC. These findings were not validated by another study, in which both NLR and LMR, but not PLR, were independently predictive of RFS in HCC associated with HBV‐related cirrhosis.…”
Section: Discussionmentioning
confidence: 96%
“…Most reports that evaluated prognostic factors for HCC patients have not included serosal invasion . Furthermore, although some reports have evaluated tumor rupture and invasion into adjacent organs, microscopic serosal invasion has rarely been assessed .…”
Section: Discussionmentioning
confidence: 99%
“…One of the reasons for this poor prognosis is the high incidence of recurrence after hepatectomy . Patient characteristics, underlying liver disease, and tumor‐related factors are reportedly prognostic factors for HCC after hepatectomy . Regarding tumor‐related factors, the number of tumors, maximum size of tumors, presence of vascular invasion, and histological type of tumors have all been reported as prognostic factors for patients with HCC .…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have investigated the relationship between PLR and mVI (Ma et al, 2016;Zheng et al, 2017). Ma (2016) performed a meta-analysis of the prognostic value of PLR in HCC and found no association with vascular invasion; however, this conclusion was based on only three eligible studies, and vascular invasion was defined as including both macrovascular invasion and mVI.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several recent studies have identified several serum inflammatory factors associated with post-treatment prognosis of HCC, including platelet-to-lymphocyte ratio (PLR) (Tian et al, 2016;Huang et al, 2017;Yang et al, 2017), neutrophil-to-lymphocyte ratio (NLR) (Goh et al, 2016;Jin et al, 2017;Urabe et al, 2017), and prognostic nutritional index (PNI) (Chan et al, 2015;Wu et al, 2016). However, only a few studies have examined the relationship between inflammatory indices and mVI (Gomez et al, 2008;Chan et al, 2015;Zheng et al, 2017). The aim of this study was to identify preoperative predictors of mVI by evaluating the correlation between preoperative clinicopathological features, including serum inflammatory indices, and mVI.…”
Section: Introductionmentioning
confidence: 99%